Coordination of EU Policy Positions in Germany and Denmark: A Politics of Institutional Choice Approach - Mads Dagnis Jensen; Peter Nedergaard; Mathias Jopp (Journal of Contemporary European Research, 2016)
This article examines the coordination mechanisms, in Germany and Denmark, which develop negotiation positions for the Council in the European Union (EU). The analysis studies these mechanisms through the lens of the ‘politics of institutional choice’ approach, which previous scholars have applied to examine EU coordination in Eastern and Central Europe. The results demonstrate that the approach travels well to EU member states in Western Europe. More pre-cisely, they show that the power of the individual ministers, as well as the type of government (minority vs. majority), are important factors in explaining differences in the way the two member states handle EU coordination. This strengthens the argument that the traits of the EU coordination mechanisms in EU member states are a function of power relations between do-mestic actors.